2008
DOI: 10.1143/jjap.47.7745
|View full text |Cite
|
Sign up to set email alerts
|

Electron Charge Density Study of (Na1-xKx)NbO3 in Cubic Structure

Abstract: The electron charge density study by synchrotron-radiation powder diffraction has been performed for the cubic structure of (Na1-xKx)NbO3 (NKN: 0≤x≤1) at 1000 K to investigate the atomic substitution effect on chemical bonding. Our precise analysis using the maximum entropy method (MEM)/Rietveld method demonstrates that the covalent bonding is formed on the Nb–O bond whereas the Na/K atoms are ionic in the entire composition range. The thermal motion of the Na ion in NaNbO3 is fairly larger than that of the K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Based on the fact that we obtained FWHM (|F MEM | − |F obs |)/ obs (F MEM : structure factors calculated by MEM analysis, F obs : observed structure factors, and obs : estimated standard deviations of observed structure factors) values of 0.172-0.192 and 0.107-0.157 by MEM of LSM and BSCF, respectively -both of which are considerably smaller than 1 -we confirmed that our MEM were correct. This value is close to that of Zr-O and a Nb-O bonds [17,18]. We assumed that these bonds possess strong covalency in LSM.…”
Section: Atomssupporting
confidence: 73%
See 2 more Smart Citations
“…Based on the fact that we obtained FWHM (|F MEM | − |F obs |)/ obs (F MEM : structure factors calculated by MEM analysis, F obs : observed structure factors, and obs : estimated standard deviations of observed structure factors) values of 0.172-0.192 and 0.107-0.157 by MEM of LSM and BSCF, respectively -both of which are considerably smaller than 1 -we confirmed that our MEM were correct. This value is close to that of Zr-O and a Nb-O bonds [17,18]. We assumed that these bonds possess strong covalency in LSM.…”
Section: Atomssupporting
confidence: 73%
“…In fact, the oxygen ion conductivity of LSM is lower than that of other perovskite oxides that are used as cathode materials for an SOFC [37]. We speculated that the (La, Sr) site in LSM has a higher valence than the Pb, K, and Na sites in these perovskites [17,18]. Mn-O plane (Fig.…”
Section: Atomsmentioning
confidence: 97%
See 1 more Smart Citation
“…A smaller t can also generate the antiferrodistortive thermal motion as observed in several perovskite-type oxides. [30][31][32][33] Although the Rietveld analysis derives only the average thermal motion, U O22 and t characteristics of seem to support the enhancement of the antiferrodistortive thermal motion in (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 in the low-temperature and high-x regions. Here, the thermal behavior of the off-centered Gd ion is discussed in further detail.…”
Section: 29)mentioning
confidence: 99%
“…Analyzing the synchrotronradiation (SR) powder diffraction data using the maximum entropy method (MEM)/Rietveld method is useful for investigating the crystal structure of cubic perovskite-type oxides ABO 3 at the charge density level. [8][9][10][11][12] Recently, the MEM/Rietveld analysis has provided direct structural evidence for the oxygen stabilization on the Bi/La-O covalent bonds in a rare-earth element La-substituted ferroelectric Bi 3:25 La 0:75 Ti 3 O 12 , which exhibits high endurance to polarization fatigue. 13) The charge density study presented in this paper will provide information essential for a better understanding of the relationship between crystal structure and ferroelectric instability in BaTiO 3 and for designing more promising BaTiO 3 systems for MLCCs.…”
Section: Introductionmentioning
confidence: 99%